That's not my T. Rex... : its tummy is too squashy - Watt, Fiona; Wells, Rachel; Figg, Non (London : Usborne Publishing Ltd, London, 2023)
An exciting title in the best-selling touchy-feely series. Turn the pages to discover the dinosaurs as they stomp through the pages of this sturdy board book. Babies and toddlers with love exploring the different tactile patches, as well as spotting the familiar little white mouse
On board pages with textured inserts.
Preschool.
Keywords: Readers; Dinosaurs -- Juvenile fiction; Tyrannosaurus rex -- Juvenile fiction; Touch -- Juvenile fiction; Picture books for children; Board books